Determinants of Stock Return and its Implications Divident Policy in Mining sector in Indonesia Stock Exchange - Hakim, Luqman; Kusmanto, Kusmanto (Utopía y Praxis Latinoamericana, 2020)
Abstract This study aims to find empirical evidence and test the influence of Indonesia Bank Certificate (SBI), rupiah exchange rate against US. dollar (KURS), operational cash flow (CFO), working capital (MK), net profit (LB), partially and jointly on stock returns, and find empirical evidence and test the effect of SBI, KURS, CFO, MK, LB, stock return (RS). This study uses two research models with a sample of 12 mining companies from a population of 40 companies listed on the Indonesia stock exchange. The analysis technique used is multiple linear regression method using the fixed effect model (FEM) in the E-View9 application.